State narcissism and aggression: The mediating roles of anger and hostile attributional bias - Li, Caina; Sun, Ying; Ho, Man Yee; You, Jin; Shaver, Phillip R.; Wang, Zhenhong (Aggressive behavior, 2016)
Prior research has documented a relationship between narcissism and aggression but has focused only on dispositional narcissism without considering situational factors that may increase narcissism temporarily. This study explored the possibility that an increase in state narcissism would foster aggressive responding by increasing anger and hostile attributional bias following unexpected provocation among 162 college students from China. We created a guided‐imagination manipulation to heighten narcissism and investigated its effects on anger, aroused hostile attribution bias, and aggressive responses following a provocation with a 2 (narcissism/neutral manipulation) × 2 (unexpected provocation/positive evaluation condition) between‐subjects design. We found that the manipulation did increase self‐reported state narcissism. The increase in state narcissism in turn heightened aggression, and this relation was mediated by increased anger. Regardless of the level of state narcissism, individuals were more aggressive after being provoked and this effect of provocation was mediated by hostile attributional bias. The findings indicate that narcissism can be temporarily heightened in a nonclinical sample of individuals, and that the effect of state narcissism on aggression is mediated by anger. Differences between state and trait narcissism and possible influences of culture are discussed. Aggr. Behav. 42:333–345, 2016. © 2015 Wiley Periodicals, Inc.